Nitrogen and Phosphorus Removal of Wastewater via Constructed Wetlands Approach - Tang, Jun Kit; Jusoh, Muhammad Noor Hazwan; Jusoh, Hisyam (Tropical Aquatic and Soil Pollution, 2023)
This study aimed to determine the efficiency of media pollutant removal from municipal wastewater with high concentrations of ammonia and phosphorus in constructed wetlands  (CWs). The study utilized secondary data from previous studies that were published in credible sources. The removal efficiencies of the five media used in the constructed wetland, namely, peat-cattails, cattails, peat, Viteveria zizanioides, and Phragmite karka, were compared. The results showed that CWs with Viteveria zizaniode exhibited the best performance on average, removing 84% nitrogen and 86% phosphorus. Peat was also effective in attenuating pH. Humic and fulvic acids in peat moss can be released quickly in an aqueous environment under alkaline conditions, effectively lowering the pH value. The combination of Viteveria zizaniode and peat significantly improved pollutant removal efficiency in municipal wastewater with high concentrations of ammonia and phosphorus.